Fred Cumberland : Building the Victorian Dream - Simmins, Geoffrey (Book collections on Project MUSE., 1997)
"In the first comprehensive study of Frederic William Cumberland (1820-1881), Geoffrey Simmins traces Cumberland's career as architect, railway manager, and politician, providing a richly detailed history and analysis of his contribution to Toronto's urban landscape." "The architect of such prominent buildings as the University of Toronto's University College, Osgoode Hall, and St James's Cathedral, Cumberland was devoted to building the Victorian dream - optimistic and materialistic in its outlook, yet also spiritual in its basis. His diverse interests and accomplishments make him an important figure in Canadian architecture and in Victorian studies more generally." "The book is divided into three parts. Part One establishes the context of Cumberland's life and times. Part Two is devoted to examining his architectural career. Part Three consists of a catalogue raisonne of all of Cumberland's architectural designs."--Jacket.